2019
DOI: 10.21608/zumj.2019.10448.1101
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Egyptian Mothers to Asthma Controllers

Abstract: Background: Objectives include evaluation of compliance of asthmatic children and their mothers through assessment of mother's knowledge, attitude, practices and behavior regarding bronchial asthma and its management at Pediatric Outpatient Clinic at Zagazig University Hospitals. Methods: A crosssectional study was conducted during the period from April 2018 to January 2019 at Pediatric Outpatient Clinic at Zagazig university Hospitals. The study included 137 mothers of asthmatic children. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Mesbah et al conducted a cross-sectional study in Egypt to examine mothers' behaviors, knowledge, attitudes, and practices regarding childhood bronchial asthma, involving over 130 participants. The study found that a majority (62.8%) of the mothers lacked sufficient knowledge about the subject [ 12 ]. Alharbi et al presented findings from a cross-sectional survey evaluating local population awareness following an asthma campaign, collecting data from 475 participants and comparing results to a 2014 report.…”
Section: Introductionmentioning
confidence: 99%
“…Mesbah et al conducted a cross-sectional study in Egypt to examine mothers' behaviors, knowledge, attitudes, and practices regarding childhood bronchial asthma, involving over 130 participants. The study found that a majority (62.8%) of the mothers lacked sufficient knowledge about the subject [ 12 ]. Alharbi et al presented findings from a cross-sectional survey evaluating local population awareness following an asthma campaign, collecting data from 475 participants and comparing results to a 2014 report.…”
Section: Introductionmentioning
confidence: 99%